VC SHARES USM SUCCESS STORY IN PLENARY SESSION, NATIONAL WORKING MEETING OF INDONESIAN HIGHER EDUCATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
SERDONG, INDONESIA, 2 February 2016 – The ViceChancellor of Universiti Sains Malaysia (USM), Professor Dato' Dr. Omar Osman was the sole head of a foreign university to be invited to attend the National Working Meeting, Indonesian Higher Education 2016 (Rapat Kerja Nasional Pendidikan Tinggi Indonesia 2016), organised by the Indonesian Ministry of Research, Technology and Higher Education (Kementerian Riset, Teknologi dan Pendidikan Tinggi) from 31 January – 2 February 2016.